Human factors engineering and its role in achieving high performance systems in light of sustainability, an analytical study - Faraj, Zainab Sabah (Eximia, 2023)
This research came in order to identify the extent of the impact of the role of human factors engineering in achieving high performance systems in light of sustainability, and the problem can be summarized as the role of human resources engineering in achieving high performance systems and sustainability. It came in the literature of human factors engineering, high performance systems and sustainability, and an attempt to know the relationship between them, and to identify the engineering of specific human factors that can be controlled to a large extent in the engineering design process that supports administrative work that aims to improve good performance through the application of the principles of designing the operations system. The research led to a set of conclusions and recommendations, the most important of which is the need to pay attention to the qualitative variables used by researchers and practitioners.